Hello, goodbye. - Tay, Li-Cheng. (2010)
Wen’s husband is almost never around the house. His recent promotion meant a larger workload and longer, irregular working hours. Wen takes to working a a chambermaid to find the human connection she desires. Looking through guests’ belongings, the shy Wen derives a curiosity about their lives, leading her to start eavesdropping around the hotel.